Design and Construction of a Website-Based Library Information System at Battuta University - Syahputra Tanjung, Wahyu; Syahputra, Dinur; Harahap, Baginda (PT. Technology Laboratories Indonesia (TechnoLabs), 2026)
This research aims to design and develop a website-based library information system at Battuta University to address existing operational challenges. Currently, the university library still relies on traditional, manual systems for its daily operations. This conventional approach significantly hampers the overall service processes, slows down administrative workflows, and reduces the efficiency of data management. With the rapid development of modern information technology, a website-based library system is expected to drastically increase operational efficiency and enhance user accessibility for both students and staff. The research method employed in this study involves a comprehensive data collection process through direct observations and structured interviews. Furthermore, the system development applies PHP and JavaScript programming languages to build a robust, user-friendly platform. The research results successfully demonstrate that this newly developed system is fully capable of automating the tedious processes of borrowing and returning books, while simultaneously increasing seamless access to online library collections. In conclusion, the implementation of a web-based library system at Battuta University is highly effective in improving library services, optimizing data accuracy, and maximizing institutional efficiency.